Clinicopathological significance of LAT1 and ASCT2 in patients with surgically resected esophageal squamous cell carcinoma. Issue 4 (3rd March 2016) - Honjo, Hiroaki; Kaira, Kyoichi; Miyazaki, Tatsuya; Yokobori, Takehiko; Kanai, Yoshikatsu; Nagamori, Shushi; Oyama, Tetsunari; Asao, Takayuki; Kuwano, Hiroyuki
Abstract : Background: Amino acid transporters are highly expressed in various human cancers. L‐type amino acid transporter 1 (LAT1) and system alanine‐serine‐cysteine amino acid transporter‐2 (ASCT2) play a crucial role in tumor progression and survival. However, the clinicopathological significance of these transporters in patients with esophageal squamous cell carcinoma (ESCC) remains unclear. Methods: One hundred and fifty‐seven patients with surgically resected ESCC were evaluated. Immunohistochemical analysis was performed for LAT1, ASCT2, CD98, Ki‐67, and micro‐vessel density (MVD), as determined by CD34 expression. Results: LAT1 and ASCT2 were positively expressed in 59% (93/157) and 48% (76/157) of tumors respectively. LAT1 and ASCT2 expression significantly correlated with T factor, N factor, lymphatic permeation, vascular invasion, and CD98 expression. The 5‐year survival rates of LAT1‐high and ‐low and ASCT2‐high and ‐low expressing patients were 62.0% and 69.6% ( P < 0.05) and 59.6% and 70.1% ( P = 0.068), respectively. The combined positive expression of LAT1 and ASCT2 was a significant prognostic factor in univariate analysis. Conclusion: High expression of LAT1 and ASCT2 correlates with metastasis and invasion. Accordingly, these proteins could serve as prognostic biomarkers and therapeutic targets for treating patients with surgically resectable ESCC. J. Surg. Oncol. 2016;113:381–389 . © 2016 Wiley Periodicals, Inc.